GAMBARAN PERAN ORANG TUA DALAM MENGEDUKASI PROTOKOL KESEHATAN DI MASA PANDEMI COVID-19 PADA ANAK USIA SEKOLAH - Yola Afrida; Yecy Anggreny; Ennimay Ennimay (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2023)
Corona virus is an acute respiratory infectious disease caused by the Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Children are very susceptible to various diseases caused by viruses, bacteria, and microorganisms. This makes parents worry about children at school age. The best way to prevent this disease is to break the chain of transmission of Covid-19 through the role of parents. Breaking the chain of transmission can be implemented by implementing the 5M health protocol in a disciplined manner. This study aims to describe the role of parents in educating health protocols during the Covid-19 pandemic for school-age children. This research is a quantitative research with a descriptive research design. The sample of this research was 207 respondents using proportional random sampling method. Data collection was carried out using a questionnaire in the form of a google form. The analysis used is univariate analysis. The results of the study include the age characteristics of the respondents with the majority being 36-45 years (50,7%) with a minimum age of 20 years and a maximum of 65 years, the majority of respondents working as housewives totaling 79 people (38,2%), the majority of respondents last education SMA totaled 84 respondents (80,6%), washed hands 119 (57,5%), wore masks 116 (56,0%), kept distance 110 (53,1%), stayed away from crowds 121 (58,5%), limited the mobility of 119 (57,5%). The parents are expected to encourage and facilitate students in implementing the 5M health protocol consistently and that schools prepare arrangements for implementing face-to-face learning during a pandemic and provide supporting facilities for implementing 5M in schools.